2018
DOI: 10.1111/psyp.13056
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for saliencies: Emotional expectations under probabilistically and aversively salient situations

Abstract: In humans, the expectation process in decision making has not been as thoroughly investigated as the evaluation process. The present study focused on the interaction between probabilistic saliency and motivational saliency during expectation and evaluation periods using stimulus-preceding negativity (SPN) and reward positivity (RewP). Twenty healthy participants performed a modified monetary-incentive delay task under reward-approach and punishment-avoidance conditions. Each condition was characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…As this component is typically maximum in the frontal-central region, we focused on the average amplitude of six electrodes (F1, Fz, F2, FC1, FCz, FC2) was selected for analysis, as has been done in many previous studies. 33 Similarly, in line with the typical topographical features of SPN, our attention was directed towards the mean amplitude of the right frontal-central sites (F2, FC2) within the time frame of 200ms prior to the feedback presentation (equivalent to 2800~3000ms following the last keyboard response).…”
Section: Eeg Recording and Pre-processingmentioning
confidence: 96%
“…As this component is typically maximum in the frontal-central region, we focused on the average amplitude of six electrodes (F1, Fz, F2, FC1, FCz, FC2) was selected for analysis, as has been done in many previous studies. 33 Similarly, in line with the typical topographical features of SPN, our attention was directed towards the mean amplitude of the right frontal-central sites (F2, FC2) within the time frame of 200ms prior to the feedback presentation (equivalent to 2800~3000ms following the last keyboard response).…”
Section: Eeg Recording and Pre-processingmentioning
confidence: 96%
“…Another two studies found comparable cue-P3s between cues signaling a high probability (98% or 100%) of an upcoming reward and cues signaling an reward probability of 50% (Deng, Yu, Chen, & Wang, 2012;Schutte, Heitland, & Kenemans, 2019). Compared to the cue-RewP and the cue-P3, recent ERP studies have more focused on the relationship between the SPN and reward probability (Catena et al, 2012;Foti & Hajcak, 2012;Fuentemilla et al, 2013;Kamei, Kotani, & Sakuma, 2018;Megias et al, 2018;Umemoto & Holroyd, 2017;Walentowska, Paul, Severo, Moors, & Pourtois, 2018). The SPN has found to be enhanced prior to rewards with 50% probability relative to those with 75% (Catena et al, 2012;Megias et al, 2018) or 100% (Foti & Hajcak, 2012) probability.…”
Section: Introductionmentioning
confidence: 99%